A colorimetric film based on polyvinyl alcohol/sodium carboxymethyl cellulose incorporated with red cabbage anthocyanin for monitoring pork freshness. (June 2021) - Liu, Danfei; Cui, Zijie; Shang, Mi; Zhong, Yunfei
Graphical abstract: Highlights: PVOH/CMC-Na based films with red cabbage anthocyanins (RCAs) were developed. RCAs were fixed into films by electrostatic interaction and hydrogen binding. The colorimetric films with low RCAs concentration were more responsive to NH3 . Colorimetric films could be applied to detect the pork freshness. Abstract: The purpose of the research was to prepare colorimetric films based on polyvinyl alcohol/sodium carboxymethyl cellulose (PVOH/CMC-Na, CPVH) doped with red cabbage anthocyanins (RCAs). The CPVH-RCAs (PVOH/CMC-Na/RCAs) films with different RCAs contents were developed with solvent evaporation method. The Fourier transform infrared reflected that RCAs were fixed into CPVH films through the electrostatic interaction and hydrogen binding, which changed the spatial structure of the CPVH films. Field emission scanning electron microscope (FE-SEM) and X-ray diffraction (XRD) indicated that the RCAs reduced the crystallinity of CPVH films during the film-forming process and affected the compatibility of CMC-Na and PVOH. Compared with CPVH films, the presence of RCAs decreased the tensile strength (TS) and swelling index (SI), and increased elongation at break (EAB) and water solubility (WS) of the colorimetric films. The low content RCAs of colorimetric films had high sensitivity to ammonia, but the color variations were not obvious. When applied to monitor the freshness of pork at 25 °C, the colorimetric films presented conspicuous color variations from red to bluey-green on spoilage. Therefore, the prepared colorimetric films containing RCAs had the potential to be used as an indicator of freshness and intelligent packaging.